Synthesis and evaluation of microwave absorption properties of Fe3O4/Halloysite/polypyrrole nanocomposites. (1st September 2020) - Maleki, Sajjad Tabar; Babamoradi, Mohsen; Hajizadeh, Zoleikha; Maleki, Ali; Rouhi, Mojtaba
Abstract : The Fe3 O4 nanoparticles and Fe3 O4 /Halloysite nanotubes (HNTs) were synthesised by the co‐precipitation method and Fe3 O4 /HNTs/polypyrrole (PPy) nanocomposites were synthesised by in situ polymerisation of pyrrole monomers on the surface of the Fe3 O4 /HNTs. The scanning electron microscopy images showed the uniform structure of nanocomposites. The Fourier transform infrared spectra revealed the characteristic peaks of Halloysite and PPy. The Fe3 O4 /HNTs/PPy nanocomposite exhibits a saturated magnetisation of 6.7 emu/g. The microwave absorption properties of Fe3 O4 /HNTs/PPy nanocomposites were investigated in the 8–12 GHz (X‐band) range. The value of the minimum reflection loss was obtained − 26.2 dB at 11 GHz for the 3 mm thickness nanocomposite. The results showed the absorbing bandwidth below − 10 dB was broadened to 2.3 GHz.